Buried on Avenue B : a novel - De Jonge, Peter (Harper, 2012)
After an elderly man with encroaching Alzheimer's disease confesses to his home attendant that as a long-ago junkie and petty thief he killed his partner in crime, police from the NYPD reluctantly dig up the community garden where the body is supposed to be buried. Instead of a dead man, they find the body of a carefully dressed ten-year-old boy. Tough-minded Detective Darlene O'Hara, last seen in the novel Shadows Still Remain, is on the case.